2013
DOI: 10.1104/pp.113.220921
|View full text |Cite
|
Sign up to set email alerts
|

The Agony of Choice: How Plants Balance Growth and Survival under Water-Limiting Conditions

Abstract: ORCID IDs: 0000-0001-9384-4138 (H.C.); 0000-0002-3217-8407 (D.I.).When confronted with water limitation, plants actively reprogram their metabolism and growth. Recently, it has become clear that growing tissues show specific and highly dynamic responses to drought, which differ from the well-studied responses in mature tissues. Here, we provide an overview of recent advances in understanding shoot growth regulation in water-limiting conditions. Of special interest is the balance between maintained growth and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
291
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(323 citation statements)
references
References 110 publications
(143 reference statements)
15
291
0
17
Order By: Relevance
“…Stomatal closure is one of the first plant responses to water deficit, reducing water loss by transpiration (Claeys and Inzé, 2013;Lawson and Blatt, 2014). Hence, the fast RWC and g s decrease observed in FMS CR1101 lineage since DH 4 suggests higher sensibility to water deficit.…”
Section: Leaf Water Parametersmentioning
confidence: 99%
“…Stomatal closure is one of the first plant responses to water deficit, reducing water loss by transpiration (Claeys and Inzé, 2013;Lawson and Blatt, 2014). Hence, the fast RWC and g s decrease observed in FMS CR1101 lineage since DH 4 suggests higher sensibility to water deficit.…”
Section: Leaf Water Parametersmentioning
confidence: 99%
“…Usually, productivity and drought tolerance are inversely proportional and adaptations result in wide range of growth rates to different taxa under water limited conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Physiological analyses have shown that plant growth is actively down-regulated during drought and is not limited by carbon supply (1)(2)(3). Reductions of growth help ensure survival by conserving water but can be undesirable for agriculture, as plant productivity is reduced more than need be if growth were less sensitive to changes in water status (3).…”
mentioning
confidence: 99%